Analisis Perilaku Menyakiti Diri Sendiri pada Anak Gangguan Spektrum Autisme - Khairunnisa, Winda; Rahmahtrisilvia, Rahmahtrisilvia; Mahdi, Arisul; Arnez, Gaby (Universitas Negeri Padang, 2024)
he author was inspired to conduct this research because of the large number of selfharming behaviors that appear in children with autism spectrum disorders. The main aim of this research is to analyze patterns of self-harm behavior in children with autism and find hypotheses about the causes of the behavior so that more appropriate interventions can be formulated. This research uses a qualitative approach with the research design used in this research being a single case study, and the data is analyzed using Nvivo with visual word count, project map and cluster analysis by coding the data in a functional behavior assessment which is then analyzed using Nvivo. The research subjects were 2 GSA students with self-harming behavior at SLB YPPA Bukittinggi. The results of the research show that the function of aji's behavior is access to tangible goods, escape and attention and the function of self-harming behavior that appears in alfi is automatic reinforcement (sensory stimulation).